Product Make Over Jamu Gula Asam Jam - Anggoro, Damas Aryo; Baskoro, Dimas Aryo (Jurnal Pendidikan Tata Boga dan Teknologi, 2022)
Jamu is the name for traditional Indonesian medicine or can be called herbal. Jamu is made from natural ingredients and is usually synonymous with a bitter taste and a pungent odor. This factor causes the culture of drinking herbal medicine to fade, especially among young people. The method applied is by changing the transformation of herbal medicine, which is mostly in liquid form, into a semi-solid processed food form, namely jam. Jamu that the author chose to makeover was Jamu Gula Asam because of the consideration of the suitability of taste with dessert products to attract young people. The data collection method used in this study was a questionnaire with 4 (four) levels (strongly dislike, dislike, like and really like) which was tested on 5 expert panelists. Then analyzed using quantitative descriptive techniques. The results showed that the quality of Jamu Gula Asam Jam from the aspects of color, texture, scent and taste had an average value of 18.25 which was included in the very like category. Assessment on the color aspect has a value of 17 which is included in the Like category, on the texture aspect has a value of 19 which is included in the Very Like category, the scent aspect has a value of 18 which is included in the Very Like category, and on the taste aspect has a value of 19 which is included in the Very Like category. Based on the results of this study, it can be concluded that the product innovation of jamu, jamu, and sour sugar is acceptable and feasible to become a new food commodity.